Fishes, Water and Ice. Reflections on Poetry for Children in the Last Decades - Dessardo, Andrea (Rivista di Storia dell’Educazione, 2020)
At the beginning of the 2000s Einaudi Ragazzi started the publication of «Pesci d’argento» (Silver Fishes), a poetry series for children with innovative traits, open to authorial poetry experimentation and politically aware. Nevertheless, the series changed soon its line, going back to propose, before ceasing, the classics of the national poetry, with the outstanding exception of the work by Vivian Lamarque. The essay considers also the different weight reserved to poetry in the textbooks for the elementary school after the launch of the new programmes in 1985.